Out Come of Ankle Arthrodesis with Ilizarov Method (Journal of Pakistan Orthopaedic Association, 2019)
Objectives: To determine the functional and radiological outcome of arthrodesis of the ankle using the ilizarov method.Methods:This descriptive study was conducted in Bolan Medical Complex Hospital Quetta and National institute of Rehabilitation Medicine Islamabad, from January 2015 to December 2018.Twenty patients fulfilling the inclusion criteria under went arthrodesis of the ankle using ilizarov method. At follow up visit patients were assessed clinically for pain and walking and radiologically for union.Results: A total of 20 patients with mean age 41.0 years ± 13.61 were included in our study. In 18(90%) a stable pain free ankle arthrodesis was achieved successfully after a mean ilizarov external fixator time of 147 days (range 105-195 days). There were minimal complications despite early weight bearing. No further surgery was required except in 02(10%) cases in which primary arthrodesis was not achieved.Conclusion: Ilizarov external fixator used for ankle arthrodesis give excellent stability, allowing early weight bearing without pain and results in higher rates of union with minimal post operative complications.